Longitudinal profiles of expressive vocabulary, syntax and pragmatic language in boys with fragile X syndrome or Down syndrome. Issue 4 (19th April 2013) - Martin, Gary E.; Losh, Molly; Estigarribia, Bruno; Sideris, John; Roberts, Joanne
Abstract Background Fragile X syndrome (FXS) and Down syndrome (DS) are the two leading genetic causes of intellectual disability, and FXS is the most common known genetic condition associated with autism. Both FXS and DS are associated with significant language impairment, but little is known about expressive language across domains over time or the role of autism in language development in FXS. Aims To compare three domains of language production (vocabulary, syntax, pragmatics) over time within and across groups of boys with FXS with and without autism spectrum disorder (FXS‐ASD, FXS‐O), boys with DS, and typically developing (TD) boys. Methods & Procedures Twenty‐nine boys with FXS‐O, 40 boys with FXS‐ASD, 34 boys with DS, and 48 younger TD boys of similar non‐verbal mental age living in the United States participated in the study. The Antonyms, Syntax Construction and Pragmatic Judgment subtests of the Comprehensive Assessment of Spoken Language were administered annually over 3 years. Outcomes & Results TD boys scored higher than all other groups on all three subtests; boys with FXS‐O and FXS‐ASD scored higher than boys with DS in Syntax Construction; and boys with FXS‐O scored higher than boys with FXS‐ASD in Pragmatic Judgment. Within‐group patterns varied between groups. Overall, the TD group showed significantly more change over time than all other groups. Conclusions & Implications Findings suggest that expressive language skills and growth across various domains are more impaired in boys with FXS and DS than would be expected based on non‐verbal mental age, that for boys with DS syntax is more impaired than would be expected based on intellectual disability, and that autism status affects pragmatic language in boys with FXS. Findings suggest that language production across domains should be addressed during assessment and intervention for boys with FXS and boys with DS, with differing group profiles also suggesting potentially different areas of focus.